ANALISIS SIKAP INDEPENDENSI, PROFESIONALISME, DAN PENGALAMAN KERJA INTERNAL AUDITOR TERHADAP EFEKTIVITAS STRUKTUR PENGENDALIAN INTERN PADA KSP DI KAB. PURWOREJO - , (Politeknik Sawunggalih Aji, 2020)
Credit Unions (KSP) is one of the cooperative according to Law Decree No. 25 of 1992 Article 16 of the cooperatives. In KSP there's supervisory board as an internal auditor. Internal auditors should have an attitude of independence, professionalism, and work experience who are able to influence the effectiveness of the internal control structure. This study uses primary data through a questionnaire conducted at KSP in Purworedjo. Determination of the samples was done by using simple random sampling. Questionnaires were distributed amounted to 40 copies but only 33 who responded, and of that number can be processed all. Data analysis techniques used hypothesis testing is multiple linear regression and correlation tests. The results of this study indicate that (a) the attitude of the independence of the internal auditor has a significance level of 0.004 is smaller than 0.05, which means a positive and significant influence on the effectiveness of the internal control structure (b) the professionalism of internal auditors has a significance level of 0.008 is smaller than 0.05, which means positive and significant impact on the effectiveness of the internal control structure (c) work experience internal auditor has a significance level of 0.000 is smaller than 0.05, which means a positive and significant influence on the effectiveness of the internal control structure (d) the correlation between the independence of the internal auditor's attitude to the effectiveness of the structure internal control was 0.716 which means that the relationship is positive in the direction (e) correlation between the professionalism of internal auditors with the effectiveness of the internal control structure of 0.759 means that the relationship is positive in the direction (f) the correlation between the internal auditor's work experience with the effectiveness of the internal control structure of 0.732 is positive means the relationship is unidirectional. Keywords: Attitudes Independence, Professionalism, Work Experience, Effectiveness of Internal Control Structure, KSP.